Development of next generation hemagglutinin-based broadly protective influenza virus vaccines. (August 2018) - Nachbagauer, Raffael; Palese, Peter
Highlights: Current influenza virus vaccines do not adequately protect against disease. Substantial progress in vaccine development has been made in the last decade. Potentially broadly protective influenza virus vaccines are currently in clinical trials. Abstract : Influenza viruses are a severe threat to human health and current vaccines do not provide sufficient protection. The highly variable nature of influenza viruses has made the production of efficacious vaccines a challenge. In recent years, a multitude of novel, broadly reactive influenza virus vaccination approaches have been described. What has long seemed impossible could now become reality in the near future — a new generation of influenza virus vaccines that provides long-lasting and broad protection against seasonal as well as potentially pandemic influenza virus strains. This review will discuss new hemagglutinin-based vaccines and their current stage of development.